Poverty Reduction through Local Wisdom(A Case Study from Buru Island-Maluku and Surade-West Java) - Pattinama, Marcus J. (UI Scholars Hub, 2009)
Literature reviews on the concept of poverty and local observation on the field study were employed to investigate who the poor are, in order to seek alternative policies according to specific local conditions to combat poverty, and to see local wisdom in a preventive effort to reduce poverty. Survey methodology, in-depth interviews and focus groups discussions were used in this study. The findings suggest that the concept of poverty is multifacet. Both Bupolo people and Surade farmers cultivate small land. While Surade farmers are poor with no or limited land size and with relatively small scales' business, Bupolo people have relatively larger land size but have limited technology access, and less access to social economic infrastructure, making them poor and only able to survive with food daily. The concept of poverty needs to be extended to include access to social economic infrastructure, remoteness, disempowerment, freedom of speech, and fairness in development. Poverty cannot be defined individually solely from the context of the calorie fulfilment as a standard used by BPS. However, in principle, the concept of poverty cannot only be defined as a relative, but also dynamic concept.